KfW Water Symposium 2009 : Financing Sanitation (2010)
"The central objective of the International Year of Sanitation was to put the global community on track to achieve the Millennium Development Goals MDG sanitation target. However, one year later, it is still difficult to keep sanitation high on the agenda, while practical action is required to encourage demand driven and sustainable solutions. With the support of the German Ministry for Development and Cooperation and together with the European Investment Bank EIB and the French Development Agency AFD, KfW organised a two day Symposium to specifically address ways in which financing institutions can better promote the achievement of the MDG sanitation target. More than 70 experts from various backgrounds explored the challenges of sanitation and discussed ways to further develop innovative financing mechanisms for improved hygiene, sanitation and wastewater management in low-income countries. Four thematic areas were tackled by detailed background papers, presentations and high-level open floor discussions. Session 1: Financing Change in Personal Hygiene Behaviour and Demand Creation for Sanitation Motivation This section contains a rapid review of past experiences in developed countries and the evolution of methods used in developing countries to change hygiene and sanitation behaviors, including successes and failures. Relative costs and impacts, the role of institutional arrangements and actors, as well as approaches for linking hygiene behavior change and sanitation demand creation (so called software investments) with hardware investments are examined. Finally, considerations and opportunities for development banks and other financing agencies to become engaged in the scale-up of hygiene behavior change and sanitation demand creation approaches which have demonstrated success are presented. Session 2: Targeting the Poor with Facilities and Improved Services Motivation The interventions that can help poor people to access sanitation goods and services are examined. The focus is on three types of interventions: the use of low-cost technologies, the use of micro-credit and the use of targeted public finance (or subsidies) to reduce the funding gap that poor people face to meet the capital and recurrent costs of sustainable sanitation. Targeted public finance, performance assessment, effectiveness, sustainability, public funding strategies and performance are analysed. Session 3: Urban Spaces - How to Provide and Finance Service to Peri-urban Areas New approaches to meet sanitation challenges arising from absolute population growth and rapid urbanization are examined from a technical point of view. Simplified solutions and semi-centralised supply and treatment systems are examined in detail and with the help of examples. Session 4: The Potential Role of Utilities in Sanitation Provision for Peri-urban Areas and Poor Target Groups The question why sanitation service provision by local government authorities is poor is addressed. Examples of how water supply and sanitation utilities are being encouraged to support peri-urban areas and poor target groups with the provision of sanitation services are provided. The difficulties of utilities to provide piped water and sewers in a commercially viable manner is addressed. The role of local government authorities, of the regulatory framework, of education and public awareness is highlighted. A theme that appeared in all four sessions concerned the process of project design by development banks. Recommendations to improve it in order to best tackle sanitation issues were as follows: 1. address the entire sanitation chain 2. plan for all urban areas including informal housing areas and slums 3. ensure the sustainable operation of all sections of the sanitation chain (long-term effectiveness). For the full proceedings and the main findings and recommendations, please visit www.iwaponline.com to download free of charge."